DEVELOPING ULARMATIKA MEDIA IN TEACHING TWO DIMENSIONAL FIGURE FOR THIRD GRADE OF STUDENTS WITH HEARING IMPAIRMENT IN THE ELEMENTARY SPECIAL EDUCATION - maharani, adinda ayu (Jurusan Pendidikan Luar Biasa, 2017)
Developing Ularmatika Media in Teaching Two Dimensional Figure For Third Grade of Students with Hearing Impairment in the Elementary Special Education. The purposeof this researchis to develop a game media of mathematics on twodimensional figure materials for third grade students with hearing impairment in elementary special education. The results, the media is well-used and can improve studentss performance. It is shown from the percentage of the average revenue validation expert reached 85,99% with qualifying very valid and the percentage of the average appraisement try out questionnaires reached 87,5% with qualifying very valid.